Epigenetic regulation in B-cell maturation and its dysregulation in autoimmunity. Issue 7 (July 2018) - Wu, Haijing; Deng, Yaxiong; Feng, Yu; Long, Di; Ma, Kongyang; Wang, Xiaohui; Zhao, Ming; Lu, Liwei; Lu, Qianjin
Abstract B cells have a critical role in the initiation and acceleration of autoimmune diseases, especially those mediated by autoantibodies. In the peripheral lymphoid system, mature B cells are activated by self or/and foreign antigens and signals from helper T cells for differentiating into either memory B cells or antibody-producing plasma cells. Accumulating evidence has shown that epigenetic regulations modulate somatic hypermutation and class switch DNA recombination during B-cell activation and differentiation. Any abnormalities in these complex regulatory processes may contribute to aberrant antibody production, resulting in autoimmune pathogenesis such as systemic lupus erythematosus. Newly generated knowledge from advanced modern technologies such as next-generation sequencing, single-cell sequencing and DNA methylation sequencing has enabled us to better understand B-cell biology and its role in autoimmune development. Thus this review aims to summarize current research progress in epigenetic modifications contributing to B-cell activation and differentiation, especially under autoimmune conditions such as lupus, rheumatoid arthritis and type 1 diabetes.